Railroad Over-Capitalization - Ripley, W. Z. (Quarterly Journal of Economics, 1914)
Over-capitalization in (1) construction, 602. — (2) Replacement of property as inviting stock-watering, 602. — Incompetence or fraud, 603. — The Rock Island and Boston & Maine affairs, 604. — (3) Division of an accumulated surplus, 606. — Indirect devices therefor, 607.— Magnitude of railway surpluses, 608. — Equitable interest of the public therein, 609. — The opposing views stated, 610. — The just intermediate opinion, 611. — The Massachusetts gas companies, 613. — Difficult to apply in practice, 614. — (4) Refunding as a concomitant of inflation, 616. — (5) Stock-watering incidental to consolidation, 617. — Financial advantage of mergers, 618. — The New Haven collapse, 619. — Connecticut trolley finance, 620. — The Rhode Island companies, 621. — The Boston & Maine road and the Westchester Co., 622. — (6) Reorganization and stock-watering, 624. — The Third Avenue Railroad case, 626. — Conclusion, 628.